Model Pembelajaran Bahasa Arab Terpadu di Perguruan Tinggi Keagamaan Islam Negeri - Supardi Supardi (LISANIA: Journal of Arabic Education and Literature, 2018)
This article explores the significance of language skills integration generally in foreign language teaching and particularly in Arabic. This is motivated by the reality of Arabic language learning in Indonesia State Islamic Higher Education (PTKIN) which still separates the four language skills so that learning Arabic language is not able to produce language learning actively as a means of communication. Through literary studies, the author offers the integration of language skills as an alternative solution in shaping communicative language learners.